2015
DOI: 10.1097/jac.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

NHS Health Checks

Abstract: Cardiovascular disease is the leading cause of mortality and morbidity worldwide. In England, the government has adopted a population-wide prevention program for cardiovascular disease, the NHS Health Check program. The program has sparked controversies over the evidence base and feasibility of implementation. We aim to provide an update on the debate and program implementation. In conclusion, the evidence base for the NHS Health Check program has a number of uncertainties and program delivery has been subopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Fourth, diversity cases from foreign countries, such as the WISEWOMEN project in the United States and the National Health Service Health Check Program (Putting Prevention First) in the United Kingdom, can be references for resolving health inequality issues. 27 28) …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, diversity cases from foreign countries, such as the WISEWOMEN project in the United States and the National Health Service Health Check Program (Putting Prevention First) in the United Kingdom, can be references for resolving health inequality issues. 27 28) …”
Section: Discussionmentioning
confidence: 99%
“… 24 , 41 Since its inception in 2008, the Health Check programme has been criticized for failing to attain the originally projected participation rates upon which initial estimates of cost and clinical effectiveness were based. 42 Further exploration of how potential socio-demographic determinants of Health Check uptake may be modified by GP surgery-related factors is now required to ensure that the programme not only achieves its aim of reducing vascular disease incidence in the population but does so without increasing health inequities between population subgroups. 42 This latter priority has been highlighted in a number of existing publications examining uptake and response to the programme, with no clear conclusions on equity so far drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Since its initiation in 2009, the policy of providing NHS Health Checks to 40–74 year olds every 5 years with the aim of reducing the risk factors associated with heart disease, stroke, type 2 diabetes, kidney disease and some types of dementia has proved controversial (Abdalrahman and Soljak 2015). Despite the Department of Health’s initial, hypothetical, cost-effectiveness analysis suggesting the policy was highly cost-effective, recent independent research has shown both a poor level of coverage (Robson et al 2016) and overall programme performance substantially below initial targets in terms of reduction in cardiovascular disease risk factors (Chang et al 2016).…”
Section: Introductionmentioning
confidence: 99%